Integrating science with mathematics & literacy : new visions for learning and assessment - 280186 Hammerman, Elizabeth L.; Musial, Diann; Hammerman, Elizabeth L., Classroom 2061 (Thousand Oaks, CA : Corwin Press, 2008)
Includes bibliographical references (p. 167-172) and index